CHOICE OF TECHNOLOGIES FOR MANAGEMENT OF CORPORATE INTEGRATION OF INDUSTRIAL ENTERPRISES - Гуцалюк, Олексій Миколайович; БОНДАР, ЮЛІЯ; Григораш, Станіслав Юрійович (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2023)
The article discusses information technologies for managing corporate integration of industrial enterprises and approaches to managing corporate integration in creating a system and strategic plan for achieving goals in managing industrial enterprises. It was determined that the development of modern corporate information systems is due to the need for more detailed information about the market and consumers; collection and use of various information; the need for close mutual contact with consumers, i.e. establishing internal communication; in-depth development of information technologies. The corporate governance system is considered, which takes into account the specific characteristics of the enterprise, the main features of which are the structure of the enterprise’s business units and the presence of such management bodies as the general meeting of shareholders, the board of directors, and the board. directors and the audit committee, which are called legal entities. Technologies and approaches that can be combined to create a complex management system for corporate integration at industrial enterprises are analyzed. It should be noted that flexibility and readiness for change play an important role in ensuring success in this area, ensuring that technology and business needs are constantly evolving. The main content of such technologies consists in simplifying and automating management processes, providing data and information exchange between other divisions of the enterprise, partners and customers. Attention is also focused on the fact that effective management of corporate integration of industrial enterprises plays an important role in increasing productivity, reducing costs and increasing competitiveness. For the formation of a complex of innovative technologies for each enterprise, it is necessary to understand that the typical templates are diverse, since the hierarchy of technologies does not have stable (quantitative) boundaries that clearly distinguish the levels of management and technological maturity, and the selection and implementation of a complex of innovative management methods are integrators formed by dynamic development of each enterprise.